PENGAJARAN MORAL DALAM BUDAYA TEPUNG TAWAR MELAYU SUMATERA UTARA - Hamidah, Hamidah (FORUM PAEDAGOGIK, 2014)
Moral teaching is very important given to every citizen with the aim of creating moral citizens. Moral teaching can be done formally through school, and can be non-formal approach to the moral values of a culture. One culture in North Sumatra is the Malay culture using Tepung tawar. Moral values contained in the symbolic procession of tepung tawar are peace, perseverance, independence, relationship, robustness, sincerity, and resignation to God Almighty.